The Role of 4C in Preparing the Golden Generation of 2045 - Qomari Romadhon, Muhammad; Qomariyah, Nurul; Muthmainna, Aqila; Febrianto, Andre; Milda, Jefpi; Izzah Khairunnisa, Fadhilah (Corolla International Conference, 2024)
This study explores the integration of 4C skills—Critical Thinking, Communication, Collaboration, and Creativity—into Indonesia’s education system as a strategic effort to prepare for the "Golden Generation 2045." Using a systematic literature review, the research synthesizes academic studies, policy reports, and global best practices to provide a conceptual framework and actionable recommendations. Critical Thinking is emphasized for problem-solving, requiring shifts toward project-based learning and critical pedagogy, while Communication skills are deemed essential for global engagement, focusing on intercultural competence and digital literacy. Collaboration, vital for teamwork and innovation, advocates curriculum designs that promote inclusivity and team-based learning, while Creativity highlights STEAM initiatives and arts integration for fostering innovation. The findings reveal challenges such as inadequate teacher training, resource limitations, and cultural barriers, calling for experiential learning, cross-disciplinary approaches, and technology use to address these gaps. This research provides a roadmap for educators, policymakers, and stakeholders to transform educational practices, equipping Indonesia’s youth with the competencies needed for global competitiveness and societal advancement.